Observation of giant magnetocaloric effect under low magnetic fields in EuTi1-xCoxO3 - 孙启磊;莫兆军;沈俊;黎玉进;李兰;张君凯;刘国栋;唐成春;孟凡斌 (中国物理B：英文版, 2017)
The magnetic properties and magnetocaloric effect（MCE） in EuTi1-xCoxO3（x = 0, 0.025, 0.05, 0.075, 0.1） compounds have been investigated. When the Ti^4＋ ions were substituted by Co2＋ions, the delicate balance was changed between antiferromagnetic（AFM） and ferromagnetic（FM） phases in the EuTiO3 compound. In EuTi1-xCoxO3 system, a giant reversible MCE and large refrigerant capacity（RC） were observed without hysteresis. The values of -△SM^max were evaluated to be around 10 J·kg^-1·K^-1 for EuTi0.95Co0.05O3 under a magnetic field change of 10 kOe. The giant reversible MCE and large RC suggests that EuTi1-xCoxO3 series could be considered as good candidate materials for low-temperature and low-field magnetic refrigerant.